Itseseuranta ja minä: kuntoilevien opiskelijoiden luottamus itseseurantalaitteisiin - Mikkola, Sami (2025)
Achieving health benefits through self-tracking devices, such as smart watches or rings, could lead to savings in public health services. However, users of self-tracking devices do not properly commit to using these devices to achieve these long-term goals. Thus, this master’s thesis aimed to map factors related to committing to these devices from the point of view of everyday life, trust, and relation to self. The first part of this thesis was conducted as a narrative review first focusing on self-tracking. The second part of the review concentrated on philosopher Michel Foucault, his oeuvre, and related literature with a focus on subjectivation, the way in which a subject objectifies itself via a moral. This concept was also applied to self-tracking. The empirical part of the study was based on the forementioned concept. Thematic interviews were conducted by interviewing six exercising university students who had used either or both a smart watch or a smart ring for at least two years. Different goals, expectations, and roles for the devices were recognised from the interviews. Based on this and literature, an expectation-based model of establishing trust was designed. Previously, at least in the case of trust, expectations have not been emphasised in such manner. Also differing from previous research, the interviews regarded everyday life exceptions, such as festivities, illness, and vacation. Thus, new perspectives were considered. Based on the interviews and literature, 15 distinct roles for self-tracking devices were identified. These could be used in managing expectations in marketing, for instance. The roles vary depending on the use and trust towards the device. The devices are mostly active and increase user agency, although excessively trusting the device causing dependency can reduce agency. Especially considering the future could be beneficial. Of the identified roles, especially “healthcare professional” and “coach” should be studied further. Their health-oriented and proactive approach in addition with customisable and long-term goals recommended by the self-tracking devices could be key to improving user commitment to these devices by better aligning with users’ expectations and goals.